Upaya Meningkatkan Kemampuan Guru dalam Proses Pembelajaran Melalui Pendekatan Supervisi Klinis - Fransina Silpa Songjanan (CV. Syntax Corporation Indonesia, 2021)
In order to improve the quality of education, there have been many efforts made by the government such as the procurement of educational infrastructure facilities, training teachers in accordance with the fields mastered, the implementation of teacher qualifications, teacher certification, and so on, but currently still has not shown improvement in the quality of education which means being reviewed from the quality of the specified standards. The purpose of this study is to find out whether clinical supervision can improve the ability of teachers in the learning process in state high schools 5 tual. In this study used the method of population studies. Population studies are the whole subject of the study. The findings of this study are: the annual program of criteria is very good. The semester program is very good. The syllabus criteria is very good. The teaching program plan (RPP) criteria is good. The teaching agenda of the teacher criteria is very good. Completed Cycle II, there is an increase both in terms of teacher readiness to make learning planning and teacher readiness in teaching but still need to be improved so that it can achieve maximum value. The list of criteria is very good. The list of criteria values is good. The improvement and enrichment program criteria are good. The initial activity of learning the criteria is very good. The core activities of learning criteria are good. The closing activities of the criteria are very good